2012
DOI: 10.2298/vsp1202175s
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of a Serbian version of the “Oral Impacts on Daily Performance (OIDP)” index - assessment of oral health-related quality of life

Abstract: Based on these results, we can conclude that this index is suitable for use in everyday practice in Serbian speaking area providing useful information required to assess oral health-related quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…This finding contradicts those of other studies (5,6,10). Most previous studies reported that dental pain was the most common orofacial pain (5,17,25). Toothache is the most frequent reason to seek urgent dental treatment.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…This finding contradicts those of other studies (5,6,10). Most previous studies reported that dental pain was the most common orofacial pain (5,17,25). Toothache is the most frequent reason to seek urgent dental treatment.…”
Section: Discussionmentioning
confidence: 62%
“…Among the 319 respondents, 101 reported orofacial pain (34% of medical students and 28% of technical sciences students). Orofacial pain is more common in young adults and least prevalent among persons older than 60 years (2,16,17). A study of the association of profession with the prevalence of orofacial pain found that the the high-risk groups were students, housewives, and persons with occasional employment (18).…”
Section: Discussionmentioning
confidence: 99%
“…Among the scales that measure the impact of oral health on daily activities of adolescents for their reliability and validity in different cultural environments the one that stands out is "Oral Impacts on Daily Performances" (OIDP) 5 . Serbian version of OIDP was introduced in 2012 and applied to geriatric population 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Beside Croatian, the OIDP was cross-culturally adapted from English into many languages 4,5,16,[25][26][27][28][29][30][31] and also showed good psychometric properties. Its version for children (Child-OIDP) was developed in 2004 32 .…”
Section: Discussionmentioning
confidence: 99%